Tinjauan awal potensi ketidakstabilan cerun dan cirian fiziko-kimia tanah di Cameron Highlands, Pahang : Preliminary survey on potential slope instability and soil physico-chemical characteristic in Cameron Highlands, Pahang - Zulfahmi Ali Rahman; Sahibin Abd. Rahim; Jasni Yaakob; Wan Muhd Razi Idris (Universiti Kebangsaan Malaysia, 2007)
Geologically Cameron Highlands was formed by a granite batholith intruding into the older sedimentary rocks. Intrusion of this acidic igneous rock formed metasedimentary rocks and other metamorphic rocks as roof pendants. The schist had been highly weathered, coloured bright grey to dark grey having fine to medium size grains with an obvious foliation. Meanwhile the granitic rock is composed of quartz, feldspar and biotite and/or tourmaline grains. Most of the road slopes cut across the granite body and slope instability survey was carried out based on type of failure, geometry and physico-chemical properties of soil slopes. Field observations showed that most of the failed slopes were soil slopes, and the slip that occurred were either shallow slip or deep slide types. Among the factors that influenced slope instability were slope geometry such as slope height and steep slope gradient, friable features of the weathering profile and the lack of surface vegetation cover. This rendered the slope surface exposed to the direct raindrop impact. Surface water run-off has also caused the development of erosion gullies on soil slope surface. Physico-chemical properties of slope material such as particle size distribution, pH, organic matter content, iron oxide content, water content, true and bulk density, and porosity were also influential in slope stability of the slopes investigated. Low soil pH (acidic) of all the slopes examined decreased iron oxide content of soil which acted as a cementing agent to soil aggregates. This has caused the soil aggregate to become weaker and easier eroded.